Responsibility of the Onerous Inheritance Waiver and Its Heirs Against the Inheritance Creditors - Doruk Gönen (İstanbul Hukuk Mecmuası)
An inheritance waiver agreement is a contract between the deceased and the probable heir and deals with the partial or complete renunciation of the inheritance right of the presumptive heir. If the party waiving their inheritance right receives a benefit in return for making a waiver agreement, this contract may cause creditors to suffer losses if the debts of the estate cannot be met from the estate. Article 530 of the Turkish Civil Code aims to eliminate this detriment to the creditors of such an estate. According to the article, if the debts of an estate cannot be met by the estate at the time the inheritance proceedings begin and the debts are not paid by the heirs, the waiver and heirs become liable to the creditors of the estate to the amount of their enrichment at the time the inheritance proceedings begin regarding the wealth they had received in the five years prior to the death of the deceased in return for the waiver. As can be seen, in order to implement Article 530 of the Turkish Civil Code, the estate must first of all be unable to meet the debts at the time the inheritance proceedings begin. Secondly, any debt that cannot be met from the estate must also not be paid by the heirs. The third condition for implementing the provision of Article 530 is that a gain must have been made by the person renouncing the inheritance in accordance with the waiver agreement and within five years prior to the death of the deceased.